Job Satisfaction, Organizational Commitment and Turnover Intention of Employees: A Malaysian Financial Institutions Perspective - Lim, Selwyn Jen Kid (2008)
The competition fir customers' wallet is intensifying rapidly as the industry undersoes yer another structural change in the form of further liberalization, which led to the introduction of new players and investors. Since the industry involves the provision of services, human capital is of utmost importance. The competition for talent in intense and financial goals. Therefore, it is important to analyze the turnover intention of employees in the Malaysia financial institutions so that policies can be implemented or improved to enable the organization to retain talent while attracting newer ones. A combination of qualitative and quantitative approach was used to obtain data to achieve the research objective. A qualitative research was conducted by interviewing 3 employees who are currently working for a Malaysian financial institution. From the research, it was concluded that the stress level has increased over time, employee turnover is a problem, satisfied and committed employees may have intention to leave their organization while those not satisfied and committed may not have intention to leave their organization. A quantitative research was conducted by obtaining 103 respondents for a questionnaire designed to determine current job satisfaction, organizational commitment and turnover intention levels in Malaysian financial institutions. From the research, it was concluded that the sampling population was generally satisfied with their jobs, committed to their organization and no intention to leave. Marital status, length of professional experience and tenure of employment with current organization have predictive ability towards the three concepts in varying degrees. Job satisfaction and organizational commitment were found to be positively related but are weak predictors of each other. Job satisfaction and organizational commitment are negatively related to turnover intention while the latter was found to be the stronger predictor of turnover intention as compared to the former. Based on the findings of research, some recommendations have been suggested to migrate the problem of employee turnover, study limitations and suggestions for future research are the discussed.